Spatial transformation in the urban periphery - a study of Lubhu, Lalitpur - Bajracharya, Rijina (Journal of Science and Engineering, 2017)
Cities are in a constant state of transformation. With the growing urbanization, spatial structures are developed or replaced by the new one with respect to time. The towns located at the urban periphery of such city centers have always been the foremost target space to cater the increasing urban growth. Thus the settlement pattern, spatial structures and cultural integrity of those towns are exposed to an inevitable process of transformation along with modernization. However, the issues of transformation may vary depending on the context. Thus the aim of the research (which is based on the household survey of 2010 A.D.) is to understand the spatial transformation and identify the issues in this transformation process in Lubhu, one of the traditional towns in Kathmandu Valley, located in the close proximity of urban boundary of Lalitpur. Since the town has two major aspects of spatial layout, the first being the traditional old settlement confined within the town gates at four cardinal directions and next the agricultural land beyond the traditional boundary, the research makes an attempt to analyze transformations namely an intensive (within the existing settlement) and an extensive (in peripheral agricultural land) transformation with some exemplary illustrations. The theoretical framework derived after the literature review facilitates the analysis of the spatial transformations happening in Lubhu.